2010
DOI: 10.1007/s10735-010-9299-x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution and expression of paraoxonases and chemokines in mouse: the ubiquitous and joint localisation suggest a systemic and coordinated role

Abstract: A vicious cycle between oxidation and inflammation leads to complications in a growing number of disease states. Knowledge on tissue distribution of chemokines, mediators of inflammatory response, and paraoxonases, with antioxidant and anti-inflammatory actions, may be relevant. Using immunohistochemistry and quantitative real-time PCR we have investigated the distribution of PON1, 2 and 3, CCL2, 7, 8 and 12 and the chemokine receptor CCR2 protein and mRNA in 23 tissues from C57BL/6J mice. As expected, PON1, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 29 publications
(30 reference statements)
1
34
0
Order By: Relevance
“…The PON1 and PON3 genes are expressed in many cell types (8) , and their protein products are found in the circulation bound to HDL (9) . Conversely, PON2 is an intracellular enzyme that is not, however, found in plasma (10) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PON1 and PON3 genes are expressed in many cell types (8) , and their protein products are found in the circulation bound to HDL (9) . Conversely, PON2 is an intracellular enzyme that is not, however, found in plasma (10) .…”
Section: Introductionmentioning
confidence: 99%
“…MCP-1 is central to the infl ammatory response as a mediator of monocyte recruitment into tissues and their subsequent differentiation into macrophages (12) . Several lines of evidence suggest that PON1 and MCP-1 coordinately regulate the infl ammatory response (8,13) . Clinical studies suggest that circulating MCP-1 concentration or serum PON1 lactonase and esterase activities, or both, may be biomarkers of a variety of diseases involving an infl ammatory response to an increased oxidative stress (14 -18) .…”
Section: Introductionmentioning
confidence: 99%
“…The genes for all 3 members of the family are widely expressed in mammalian tissues [6], however, PON1 and PON3 are predominantly located in the plasma associated with high-density lipoprotein (HDL) while PON2 is not found in the plasma but has a wide cellular distribution [7]. PON1, PON2 and PON3 all retard the proatherogenic oxidative modification of low-density lipoprotein (LDL) and cell membranes and are therefore considered to be antiatherogenic [8].…”
Section: Introductionmentioning
confidence: 99%
“…Chemokines, CCL2 in particular, are central to the vascular inflammatory response as mediators of monocyte recruitment into the arterial wall [24]. Previous studies found that PON1 inhibits the production of CCL2 induced by oxidative stress in cultured endothelial cells, and that both PON1 and CCL2 are ubiquitously distributed in mouse tissues and, as such, implying combined systemic effects [25,26]. Clinical data suggest that plasma CCL2 concentration measurement may be an important biomarker of diseases involving inflammatory response to an increased oxidative stress [27,28].…”
Section: Discussionmentioning
confidence: 99%